2015
DOI: 10.3390/ijms16023915
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid as a Potential Inhibitor of Plasmodium falciparum Histone Deacetylase 1 (PfHDAC1): An in Silico Approach

Abstract: A new Plasmodium falciparum histone deacetylase1 (PfHDAC1) homology model was built based on the highest sequence identity available template human histone deacetylase 2 structure. The generated model was carefully evaluated for stereochemical accuracy, folding correctness and overall structure quality. All evaluations were acceptable and consistent. Docking a group of hydroxamic acid histone deacetylase inhibitors and valproic acid has shown binding poses that agree well with inhibitor-bound histone deacetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…There are five putative HDACs in P. falciparum; PfHDAC1 (PF3D7_0925700) is the only class I HDAC representative in P. falciparum, while PfHDA1 (PF3D7_1472200) and PfHDA2 (PF3D7_1008000) belong to class II HDACs, and PfSir2a (PF3D7_1328800) and PfSir2b (PF3D7_1451400) are phylogenetically close to class III HDACs 47 . Several HDAC inhibitors with in vitro and in vivo antiplasmodial activity have been reported previously [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37,38,[57][58][59][60][61] . For instance, WR301801 was discovered via chemical modification based on the structure of SAHA and can inhibit the growth of plasmodial at a low-nanomolar range in vitro, and the selectivity index is about 1000.…”
Section: Discussionmentioning
confidence: 99%
“…There are five putative HDACs in P. falciparum; PfHDAC1 (PF3D7_0925700) is the only class I HDAC representative in P. falciparum, while PfHDA1 (PF3D7_1472200) and PfHDA2 (PF3D7_1008000) belong to class II HDACs, and PfSir2a (PF3D7_1328800) and PfSir2b (PF3D7_1451400) are phylogenetically close to class III HDACs 47 . Several HDAC inhibitors with in vitro and in vivo antiplasmodial activity have been reported previously [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37,38,[57][58][59][60][61] . For instance, WR301801 was discovered via chemical modification based on the structure of SAHA and can inhibit the growth of plasmodial at a low-nanomolar range in vitro, and the selectivity index is about 1000.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen mammalian HDACs have been identified so far [ 2 ], and have been subdivided into four different classes based on their homology with yeast HDACs. HDAC inhibitors (HDACi), such as the anticonvulsant drug valproic acid (VPA), have been identified as neoadjuvant to chemotherapy and radiotherapy [ 3 ]. The VPA-induced sensitization of tumor cells has been attributed to its effect on HDAC-dependent transcriptional repression and hyperacetylation of histones, which resulted in the differentiation of tumor cells and increased both apoptotic and non-apoptotic cell death [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focus on the class I histone deacetylase PfHDAC1, which is a prime antimalarial target [22, 23] and is critical for parasite viability [19, 23, 34]. We identified that the enzymatic activity of PfHDAC1 is governed by its posttranslational modification (serine phosphorylation) status, which is similar to what is observed for higher eukaryotic HDACs [37].…”
Section: Discussionmentioning
confidence: 91%